Membangun Kepercayaan Diri Mahasiswa di Era AI: Analisis Pengaruh Persepsi Manfaat, Sikap terhadap Teknologi, dan Pengalaman Penggunaan Kecerdasan Buatan: Building Students’ Self-Confidence in the Era of Artificial Intelligence: An Analysis of the Effects of Perceived Usefulness, Attitude Toward Technology, and Artificial Intelligence Usage Experience - Ahyar Junaedi; Andykha Mujizatryo; Jaemi Wahyudi (Anterior Jurnal, 2026)
The advancement of artificial intelligence (AI) technology has significantly transformed education, particularly in how students adapt to and interact with modern learning technologies. This study aims to examine the influence of perceived usefulness of AI, attitude toward technology, and AI usage experience on students' self-confidence at the Faculty of Business and Informatics. A quantitative approach was employed using a survey method involving 306 respondents from a total population of 842 students, selected through proportionate stratified random sampling. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique with SmartPLS version 4. The results indicate that all constructs in the model meet the validity and reliability criteria, and the model is deemed fit with an SRMR value of 0.063. Structurally, the three independent variables—perceived usefulness of AI, attitude toward technology, and AI usage experience—have a positive and significant effect on students' self-confidence, with an R-square of 0.633, explaining 63.3% of the variance in students' self-confidence. These findings highlight the importance of integrating cognitive, affective, and behavioral factors to build students' confidence in the digital era and offer strategic implications for higher education institutions seeking to enhance AI-based learning practices.